Caracterização genética de isolados do Squash mosaic virus (SqMV) e análise de imagens para avaliação da qualidade fisiológica de sementes produzidas por plantas de abóbora infectadas - Alencar, Nara Edreira (2015)
The Squash mosaic virus (SqMV) infects plants of Cucurbitaceae family and can cause frequent yield losses. Little is known about the virus population in the main Brazilian cucurbit-producing regions as well as the effect of this virus on seeds coming from infected plants. Thus, the objective of this study was to sequence and analyze the genetic diversity of SqMV isolates collected in Tocantins and São Paulo, check the possibility of using image analysis for the evaluation of internal damage and use of DAS-ELISA techniques and IC-PCR for the detection of SqMV seeds produced by infected squash plants. In order to study the genetic diversity were designed primers based on SqMV sequences available in the GenBank, to amplify a genomic fragment with 2599 nucleotides (nt) of each isolate containing part of the movement protein gene (MP), the two subunits of the capsid protein (LCP and SCP) and the 3 'UTR. The sequence analysis of 2490nt (genome coding region) showed an identity ranging from 89% to 98%, when the Brazilian isolates were compared, and 82% to 88% when they were compared with GenBank isolates. Comparing the genes, separately, the nucleotide identities were similar. However, substitutions not always resulted in amino acids changing so that identities between amino acids was over 90%, excluding GR2 MP gene, which showed an identity between 82% and 83%. In the analysis of the 3 'UTR, the MOC isolate showed the lowest identity, between 39 and 42%, and the remaining Brazilian isolates clustered separately from GenBank isolates. In most phylogenetic trees, Brazilian isolates clustered separately from the isolates used for comparison, and there was a closer relationship between the LC2 and MOC isolates, and greater distance between these isolates LC3 and FA. Among the GenBank isolates, there was a closer relationship between the EU421060 isolate from China and the AF059532 American isolate in all the trees. Closer relationship was also seen between the AF059533 American isolate and NC003 800 Japanese isolate in the trees based on nucleotides and amino acids sequences of the MP and CP1 nucleotides. In the trees based on the amino acid of the 2490 nt fragment, NC003800 Japanese isolate were closer to KP223324 Spanish isolate and the trees built for CP1 and CP2 noticed a greater proximity between the isolated American isolate (AF059533 ) and Spanish isolate KP223324. This study presents the first reports on the genomic characterization of SqMV isolates in Brazil. The image analysis for the evaluation of possible internal damage seed sorting of the seeds in three categories: empty, full and damaged. In the germination test, infected seeds classified as full seeds produced more abnormal seedlings compared to the healthy seeds of the same category. There was also a reduction in seed vigor of when they were infected with SqMV. Radiographic analysis has proved to be a useful tool in assessing the quality of seed produced by SqMV infected plants. DAS-ELISA and IC-RT-PCR methods were efficient in detecting SqMV seed. Tests involving virus transmissibility or even other investigations related to virus infected seeds can be greatly improved by using these techniques.